Pioneering exploration of the mountains expressed through architecture - Kronowski, Dariusz (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2021)
The study is designed to organize the knowledge on development of mountain architecture. It covers a time period, drawn from pioneering discoveries in the architecture and landscape of the mountains. In the thematic aspect, analized problem in the subject of tourism and shaping mountain facilities on selected examples. Included issues related to construction and the use of native materials depending on the location, as well as factors such as climate and the tradition of the place. The importance of nature and the attempt to answer how to shape architecture without interfering with the natural environment and linking nature and buildings with each other were also emphasized. Changes in architectural forms were also indicated, as well as the scope of the influence of cultural diversity and drawing on patterns. During the analysis of the topic, the author studied and collected materials directly and indirectly related to the topic. The works of mountain architecture mentioned in the text were analyzed, as well as their history and historical development. The point was presented on the basis of issues including development, as well as sections of thematic, territorial and time ranges, characterizing individual stages of the development of mountain architecture from the beginning of the existence of the studied mountain structures shaped by the culture of gathering and pastoralism to a detailed analysis prepared on the basis of mountain architecture of the 19th and 20th centuries. First, there was wood, stones, earth – the basic building blocks. Mountain architecture is often demanding, monumental with a shape characteristic of the landform, less for a regional nature, although derived from it, but also objects that create the nature and character of the place, the so-called "Genius loci". The search for fantasy as well as unique beauty – all this is an extension of the fact that mountain architecture is not only a craft with narrowly delineated borders, but a light, creative and uninhibited art. In orderly contrast, the shape is subject is to the opposite of chaos, to the control of order at the edge of the design process. In buildings which characterized by a contrast to the surroundings – geometry and form, as well as structure are the way to non-accidental architecture in difficult conditions. Architecture hidden in the field, introverted, closed in the world that frees the recipient from the daily disorder. It is pure pioneering work of architects without architecture creating objects from imitation, such as huts and typical mountain shelters based on pure regionalism. In mountain architecture, you can agree to three basic varieties: Architecture from imitation – mimesis – the principle of creative imitation Architecture - harmonic, unique patterns Architecture in conscious contrast